Quest for Philosophical Groundings of Affirmative Action Policy - Maurya, Sooraj Kumar (Frontiers in Law, 2025)
From its inception to the present, affirmative action has been a never-ending issue. Despite being endlessly debated since its inception, an unmistakable agreement on whether or not a nation’s government can implement affirmative action policy appears to have gone unnoticed thus far. Affirmative action is a public policy that seeks to compensate victims of past injustice at the expense of others’ possession. This is why it is viewed negatively in terms of equality and possessive individualism. At best, a few fashionable philosophers, such as John Kekes and Carl Cohen, do not believe in affirmative action policy because it, explicitly or implicitly, discounts the equality opportunity principle. In contrast to the position, some thinkers, such as John Rawls, believe that affirmative action policies for the disadvantaged and under-represented should be implemented. The purpose of this paper is to provide a philosophical understanding of affirmative action policy by constructing affirmative action policy’s positive (favouring) and negative (disfavoring) arguments. The author’s position on this issue will be advanced at the end of the paper.